Determining Asphalt Binder Aging by Using Limiting Phase Angle Temperature - Kristjan Lill; Karli Kontson; Andrus Aavik (The Baltic Journal of Road and Bridge Engineering)
This paper discusses the applicability of using limiting phase angle temperatures, measured in the Dynamic Shear Rheometer, to assess the aging of asphalt binders. In terms of pavement management, it is of high value for road owners to know the aging condition of the binder present in a pavement. For this purpose, 37 binder samples were collected, including tank samples and others extracted from loose mixture or core samples. Based on these samples, the findings indicate that the T(30°) parameter can successfully be used to measure the aging of asphalt binders. A key discovery was that the T(30°) parameter was able to detect a substantial change in asphalt binder quality which was missed by the current European asphalt binder specification. Newer binders are found to be more elastic than binders used around five years ago. This indicates that the binder in older pavements is of high value and the recycled asphalt pavement obtained from these pavements could even enhance the performance of new mixtures. Additionally, the effect of different aggregate types to the aging of asphalt binders was studied, but no definitive conclusions could be drawn. Furthermore, it was found that, in most cases, the Rolling Thin Film Oven Test resulted in more severe aging of asphalt binder compared to aging in the asphalt mixing plant. A correlation between the T(30°) parameter and defects on the pavement was investigated, but correlation was found to be negligible.